Current problems fine arts education in primary school - Igor Bai (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the problem of diversity of the content of education, the organizational forms of studies, pedagogical, training methods at the Fine Arts lessons.  The problems of teaching quality and the ways of improvement of pupils' artistic activity are exposed in this article. Key words: artistic image, integration of arts, descriptive activity, creation, image.